Host‐Assisted Delivery of a Model Drug to Genomic DNA: Key Information from Ultrafast Spectroscopy and in silico Study. (11th March 2022) - Ghosh, Ria; Singh, Soumendra; Mukherjee, Dipanjan; Mondal, Susmita; Das, Monojit; Pal, Uttam; Adhikari, Aniruddha; Bhushan, Aman; Bose, Surajit; Bhattacharyya, Siddharth Sankar; Pal, Debasish; Saha‐Dasgupta, Tanusri; et al.
Abstract: Drug delivery to a target without adverse effects is one of the major criteria for clinical use. Herein, we have made an attempt to explore the delivery efficacy of SDS surfactant in a monomer and micellar stage during the delivery of the model drug, Toluidine Blue (TB) from the micellar cavity to DNA. Molecular recognition of pre‐micellar SDS encapsulated TB with DNA occurs at a rate constant of k1 ∼652 s −1 . However, no significant release of encapsulated TB at micellar concentration was observed within the experimental time frame. This originated from the higher binding affinity of TB towards the nano‐cavity of SDS at micellar concentration which does not allow the delivery of TB from the nano‐cavity of SDS micelles to DNA. Thus, molecular recognition controls the extent of DNA recognition by TB which in turn modulates the rate of delivery of TB from SDS in a concentration‐dependent manner. Abstract : Delivery of Toluidine Blue (TB) to DNA in the form of TB‐surfactant ionic pair occurs in the pre‐micellar stage of the surfactant, in contrast to the no transfer of TB molecules to DNA in the micellar stage.